Effect of agmatine on electrically and chemically induced seizures in mice - ARICIOĞLU, FEYZA (NEW YORK ACAD SCIENCES, 2003)
Agmatine, an amine and organic cation, is formed by the decarboxylation of L-arginine by arginine decarboxylase. It binds to alpha(2)-adrenergic and imidazoline receptors. It blocks N-methyl-D-aspartate (NMDA) subtype of glutamate receptors and inhibits nitric oxide (NO) synthase. Because the importance of NMDA receptors and the NO system are well known in seizure activity, this study was designed to investigate the effect of agmatine on electrically and chemically induced seizures by using maximal electroshock (MES) and pentilentetrazole (PTZ) models in mice. Initial studies established convulsive current 50 (CC50) for MES and effective dose 50 (ED50) for PTZ to produce seizures. Agmatine (20, 40, 80, and 100 mg/kg intraperitoneally) increased the threshold of seizures in MES dose dependently. In PTZ-induced convulsions, the highest dose of agmatine (100 mg/kg) increased the seizure onset time and decreased percent survival. The percentage of grade V seizures was found to be increased by agmatine doses greater than 20 mg/kg.
Keywords: agmatine; maximal electroshock; pentilentetrazole; imidazoline; adrenoceptors; NMDA; nitric oxide; NITRIC-OXIDE SYNTHASE; PROCONVULSANT; ANTICONVULSANT; RATS; NEUROTRANSMITTER; STIMULATION; INHIBITORS; RODENTS